STRATEGI PEMERINTAH DALAM MENINGKATKAN PARTISIPASI MASYARAKAT SEBAGAI UPAYA PENGEMBANGAN PARIWISATA PANTAI MALAGA - Ridhon Simangungsong; Elman Nofan Ziliwu (LPPM Universitas HKBP Nommensen, 2021)
The study was set back by a lack of participation in the development of tourism in the cities of gunungsitoli, especially those around the coast of Malaga. The study aims to learn how the gunungsitoli government's strategy in boostering community participation as an effort in developing Malaga beach tourism. The development of tourism is one of the duties and responsibilities of the government of the youth and sports tourism service. The study employs descriptive methods with a qualitative approach. The research was developed with dimensions of planning, implementation and evaluation. The research subject used in the study is the government of the youth tourism service and gunungsitoli city sports administration, the owners of Malaga beach tourism, the local community and visitors to Malaga beach attractions. The identification of the subject is using a nonsampling technique with an observsive sampling. The data-gathering techniques used were interviews, observations and documents. Based on research obtained, the government's strategy to increase community participation is the creation of a plan for development of regional tourism that involves people getting input, whether by direct or indirect socialization, and creating tools and infrastructure to optimize